Mukoepidermoid-Karzinom der Glandula Submandibularis nach hochdosierter Radioiodtherapie: Fallpräsentation und Literaturübersicht = Mucoepidermoid carcinoma of the submandibular gland after high-dose radioiodine therapy : case report and review of the literature - Henze, Marcus; Hittel, Jens-Peter; Elser, Hubert (Nuklearmedizin, 1998)
Case report of a 42 year old female, who received 14th-20th year of life six radioiodine therapies with altogether 19.2 GBq131I because of a papillary thyroid carcinoma. 17 years after the last therapy, she developed a histologically proven chronic radiogenic sialadenitis of the left submandibular gland. Further four years later, the right submandibular gland has been extirpated because of a mucoepidermoid carcinoma with infiltration of a regionary lymphatic node. Review of the previous published secondary-malignancies of the salivary glands after high-dose radioiodine therapies.